"Allocation of medical resources" - Liebert, Carl W. (Journal of religion and health, 1983)
Typical macroallocation and microallocation paradigms of medical resources are discussed. Rather than strict polarization of these two aspects of resource allocation, a spectrum of positions is emphasized that supports approaching both extremes in the same fashion. Until now many have argued for a social value oriented system for macroallocation issues while choosing randomness or queuing for the opposite extreme. I do not believe that such a distinction can be morally supported but that a consistent approach to allocation of resources should be maintained.